Analysis of survey data of breeding herd for reproductive management practices in swine farms of Punjab - SINGH, A K; SHARMA, A; SINGH, U; MAHAJAN, V; SODHI, S S (The Indian Journal of Animal Sciences, 2019)
The present survey was performed to analyze standard operating procedures for swine development and fertility based on prevailing reproductive management practices among different swine farms of Punjab. The average farrowing rate, farrowing interval, weaning to estrus interval, weaning to conception interval and age at first breeding were 71.5Â±11.4%, 165.4Â±13.8 days, 8.3Â±2.1 days, 42.7Â±11.0 days and 8.1Â±1.3 months, respectively. Mean live litter size at birth and weaning were 9.9Â±3.6 and 8.1Â±3.3 piglets per farrowing, respectively. Most farmers (94.1%) kept pigs in loose housing system with a mixture of both stalls and pens, and used cement and brick as construction material for sties. Majority of farms (84.3%) functioned as farrow to wean with intensive production systems (75.5%). The labor to animal ratio of 1:50 was most common. Accurate and well maintained records were noticed at 66.7% farms. Start of boar exposure after weaning began within 1 day, occurring most often in morning, with exposure times varying from < 2â€“5 min/sow in 87.3% farms. Natural mating was allowed within minutes to hours after detection of estrus on 100% of farms. At all farms (100%), sows were allowed ô€´1 chance for breeding after conception failure before culling. Summer infertility was observed on 56.9% of farms. Feeding method for lactating sows was divided between ad lib. and gradual daily increase of concentrate feed and kitchen waste. None of the farmer practiced docking in newborn piglets. These results suggest that reproductive management of farms in key areas related to weaning, breeding, gestation, feeding and health care could be a source of varying reproductive performance among swine.